Employers' Assessment on Training Quality and Work Response Level of Medical Graduates at Pham Ngoc Thach University of Medicine - Dang, Thị Thuỳ Linh; Tran, Thị Khánh Tường; Truong, Công Hòa; Phan, Nguyễn Thanh Vân (Journal of Technical Education Science, 2023)
This study is to evaluate the training quality and work response level of medical graduates at Pham Ngoc Thach University of Medicine from the employer's perspective. Subjects of the study are medical graduates who have been working in health facilities. The assessment is done based on a set of criteria, including work response level, attitude towards the medical profession, medical knowledge and skills, foreign language skills, IT skills and employer's satisfaction. The survey results at 18 medical units (160 respondents) showed that: Up to 86.26% of the employer assessed as responding or more (mean=4.01, SD=0.63); Most of the respondents (91.88%) assessed that the level of completion of the assigned work was quite satisfactory or higher (mean=3.89, SD =0.88); and 85.63% of the respondents were satisfied and very satisfied (mean=4.00, SD =0.59). The mean scores are high when assessing attitudes towards the medical profession (mean=3.80-4.18, SD=0.58-0.71), medical knowledge and skills (average=3.68-4.06, SD=0.52-0.70), on foreign language and IT skills (average=4.03-4.10, SD=0.58-0.62). The research results show that the training quality of the University has met the requirements of employers as well as helping the University to have a basis for making plans to improve and enhance the quality further in the future.